Comparison of the oral health indices in patients with type II diabetes with different glycemic control levels: a case-control study - Mohsen Hashemi; Shirin Hassanpour; Vahideh Sadra; Zahra Aghazadeh; Arman Amini Dehkordi; Katayoun Katebi (مجله پزشکی دانشگاه علوم پزشکی تبریز)
Background. Glycemic control and oral health have a two-way relationship. The objective of this study was to compare dental caries and gingival indices in type II diabetic patients based on hemoglobin A1c (HbA1c) levels. Methods. In this case-control study, 150 type II diabetic patients were studied in three groups with HbA1c below 7%, between 7‒9%, and above 9%. The decayed, missing, and filled teeth (DMFT) index and gingival index were determined by oral examination. Demographic variables were collected through patient files. A blood test was requested to measure HbA1c. The data were analyzed using SPSS 17, and the significance level was set at P<0.05. Results. There was a statistically significant difference in the mean number of decayed teeth (P=0.017), missing teeth (P=0.034), and overall DMFT index between the three groups (P<0.001). The mean number of filled teeth between the three groups was not significant (P=0.346). The mean gingival index in the group with HbA1c above 9% was significantly higher than the other two groups (P=0.015). Conclusion. The gingival index and DMFT increased with an increase in HbA1c. In other words, diabetes had more negative effects on gingival and dental health when its control was poorer. Practical Implications. Considering that the level of diabetes control has a great impact on oral health, it is necessary for diabetic patients, especially patients whose HbA1c is higher than 7%, to be regularly examined for teeth and gingival problems.